Towards consistent generation of pancreatic lineage progenitors from human pluripotent stem cells - Rostovskaya, Maria (Philos Trans R Soc Lond B Biol Sci, 2015)
Human pluripotent stem cells can in principle be used as a source of any differentiated cell type for disease modelling, drug screening, toxicology testing or cell replacement therapy. Type I diabetes is considered a major target for stem cell applications due to the shortage of primary human beta cells. Several protocols have been reported for generating pancreatic progenitors by in vitro differentiation of human pluripotent stem cells. Here we first assessed one of these protocols on a panel of pluripotent stem cell lines for capacity to engender glucose sensitive insulin-producing cells after engraftment in immunocompromised mice. We observed variable outcomes with only one cell line showing a low level of glucose response. We, therefore, undertook a systematic comparison of different methods for inducing definitive endoderm and subsequently pancreatic differentiation. Of several protocols tested, we identified a combined approach that robustly generated pancreatic progenitors in vitro from both embryo-derived and induced pluripotent stem cells. These findings suggest that, although there are intrinsic differences in lineage specification propensity between pluripotent stem cell lines, optimal differentiation procedures may consistently direct a substantial fraction of cells into pancreatic specification.